Activated carbon loaded with manganese and iron for glyphosate adsorption: Kinetics, isotherms and thermodynamic studies - Natalia Ueda Yamaguchi (Revista Ambiente & Água, 2019)
Granular activated carbon was loaded with 0.5% manganese and 1.0% iron (m/m) for glyphosate removal from aqueous solutions. The adsorbent material was characterized by scanning electron microscopy, dispersive energy spectrometry, nitrogen adsorption techniques and zeta potential analyses. Batch studies were performed to investigate the adsorption equilibrium, kinetics mechanisms and to obtain thermodynamic information. Glyphosate adsorption increased with the contact time and achieved equilibrium within 24 h, with a maximum adsorption capacity of 9.19 mg g-1 at 45°C. Batch kinetic experimental data obeyed the pseudo-second-order model with R2>0.99. Adsorption isotherm experiments were carried out at 5, 15, 25, 35 and 45°C. The adsorption isotherms presented a better fitting using the Freundlich model (R2>0.98), indicating a multilayer adsorption of glyphosate. Thermodynamics studies showed that the adsorption of glyphosate onto granular activated carbon loaded with manganese and iron was spontaneous and feasible with negative values of ΔG°, endothermic with ΔH° of 20.924 kJ mol-1 and ΔS° of -73.250 J mol-1 K-1, suggesting a decrease in randomness at the solid–liquid interface between glyphosate and the adsorbent. The experimental results demonstrated that activated carbon loaded with manganese and iron may be an alternative for glyphosate removal in water, wastewater treatment and purification processes.